2017
DOI: 10.1002/ange.201703270
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Friedel–Crafts Acylation and Fries Reaction

Abstract: The Friedel-Crafts acylation is commonly used for the synthesis of aryl ketones,and abiocatalytic version, which may benefit from the chemo-and regioselectivity of enzymes, has not yet been introduced. Described here is ab acterial acyltransferase which can catalyze Friedel-Crafts C-acylation of phenolic substrates in buffer without the need of CoAactivated reagents.C onversions reach up to > 99 %, and various C-or O-acyl donors,s uch as DAPG or isopropenyl acetate,are accepted by this enzyme.Furthermore the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For the evaluation of pH, the model substrate was changed to resorcinol (Fig. 6 ), since we were interested to apply this enzyme for various acyl donors and acceptors (Schmidt et al 2017 ). Thus, the ATase activity in the following studies was evaluated based on the formation of the C-acetyl product 9 arising from the bioacetylation of model substrate 8 by DAPG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the evaluation of pH, the model substrate was changed to resorcinol (Fig. 6 ), since we were interested to apply this enzyme for various acyl donors and acceptors (Schmidt et al 2017 ). Thus, the ATase activity in the following studies was evaluated based on the formation of the C-acetyl product 9 arising from the bioacetylation of model substrate 8 by DAPG.…”
Section: Resultsmentioning
confidence: 99%
“…HCl (3.6 vol%), trans -cinnamaldehyde (3.6 vol%)]. Shake flask cultivation, expression of the wild-type, and recombinant ATase was performed as described previously (Schmidt et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] The combination of photoredox/nickel catalysis recently initiated by MacMillan 11 and Molander 12 has led to advances in redoxneutral chemical bond formation. [13][14][15][16][17][18][19][20] In this context, several research groups [21][22][23][24] have reported elegant examples of metallaphotoredox-catalyzed C(sp 3 )-H acylation with amides, anhydrides or activated 2-pyridylthioesters as acyl surrogates. In these reactions, substrates such as compounds with an -C(sp 3 )-H adjacent to heteroatom or simple alkanes have been employed to cause a facile HAT process and thus control the regioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] In this context, several research groups [21][22][23][24] have reported elegant examples of metallaphotoredox-catalyzed C(sp 3 )-H acylation with amides, anhydrides or activated 2-pyridylthioesters as acyl surrogates. In these reactions, substrates such as compounds with an -C(sp 3 )-H adjacent to heteroatom or simple alkanes have been employed to cause a facile HAT process and thus control the regioselectivity. There is still, however, a great demand for the development of a practical protocol using a readily available chemical as an alkyl radical source, [25][26][27] with the aim to construct complex ketones without redundant protection and deprotection process.…”
Section: Introductionmentioning
confidence: 99%